High‐Performance Terahertz Sensing at Exceptional Points in a Bilayer Structure. Issue 9 (11th July 2018) - Jin, Biaobing; Tan, Wei; Zhang, Caihong; Wu, Jingbo; Chen, Jian; Zhang, Shuang; Wu, Peiheng
Abstract: Many intra‐ and inter‐molecular vibrations lying at terahertz (THz) frequencies in bulk, powder, and thin film, which could provide rich structure information, can be accessed by conventional Raman and Fourier transform infrared spectroscopies. However, due to the lack of high‐quality THz sources and detectors, the sensitivity that has been demonstrated with THz sensors is far from the level needed to detect small amounts of sample, like monolayer biomolecules. This puts forward an urgent requirement for a THz biosensor with ultra‐high sensitivity. Here, a theoretical design is proposed using a bilayer metasurface to construct a two‐resonator coupled system that obeys passive parity time symmetry and that possesses an exceptional point. By designing the coupled resonators to have orthogonal excitation orientations and retrieving the eigenfrequencies in polarization space, eigenfrequency splitting even smaller than the resonance linewidth can be distinguished, and thus attain ultra‐high THz sensitivity. Electromagnetic simulations show that the sensitivity, defined as the frequency change per micrometer in thickness and per refractive index unit (RIU) of the analyte, can reach 800 GHz RIU −1 µm −1, an order of magnitude higher than the values reported in previous work. This proposed high‐sensitivity approach could open a path toward the detection of monolayer molecules at THz frequencies. Abstract : A bilayer metasurface is designed to obey passive parity time symmetry and that possesses an exceptional point. With this metasurface, eigenfrequency splitting can be distinguished under tiny perturbation, even smaller than the resonance linewidth. Simulations show that the sensitivity can reach 800 GHz RIU −1 µm −1, one order higher than the previous reports, and meet the requirement of the detection of monolayer molecules at THz.